EFEKTIVITAS SOCIAL MEDIA MARKETING UNTUK UMKM BIDANG AKSESORIS BATU DI PACITAN - Setyawan, Ignatius Roni; Listyarti, Indra; Hapsari, Claudia Gita (Jurnal Bakti Masyarakat Indonesia, 2025)
Optimistic Gems (OG) Jewelry is one of the MSMEs in Pacitan Regency founded by Mrs. Istianah in 2014. OG Jewelry sells various types of jewelry made from gemstones by highlighting the richness of local natural resources. With the declining trend of gemstones since 2024, OG Jewelry needs to improve their marketing strategy, especially on social media. OG Jewelry's product marketing has been carried out through social media and holding exhibitions. OG Jewelry has an Instagram and WhatsApp Business account. OG Jewelry also actively sells its products online. OG Jewelry also collaborates with various parties, such as the government. The PKM implementation method is carried out through interactive webinars and intensive mentoring in the form of Focus Group Discussions (FGD) which were held on May 12, 2024. The PKM team provided training and consultation to Mrs. Istianah and her business partners, MSME actors in Pacitan Regency. The webinar activity also involved practitioners in the marketing field, namely Mr. Handarbeni Setio Wicaksono. The result of this PKM is an increase in their brand awareness and significant marketing effectiveness including an invitation to participate in Fashion Fest 2024. This activity was able to contribute to updating the OG Jewelry business profile to become an international MSME through superior participation in Fashion Fest 2024 and also succeeded in modifying the OG Jewelry profile on social media which had an impact on increasing engagement with customers ABSTRAK Optimistie Gems (OG) Jewelry adalah salah satu UMKM di Kabupaten Pacitan yang didirikan oleh Ibu Istianah pada tahun 2014. OG Jewelry menjual berbagai jenis perhiasan dengan bahan batu akik dengan menonjolkan kekayaan sumber daya alam lokal. Dengan menurunnya tren batu akik sejak tahun 2024, OG Jewelry perlu meningkatkan strategi pemasaran mereka, terutama di media sosial. Pemasaran produk OG Jewelry sudah dilakukan melalui media sosial dan mengadakan pameran. OG Jewelry memiliki akun Instagram dan WhatsApp Business. OG Jewelry juga menjual produknya dengan aktif secara online. OG Jewelry juga menjalin kerjasama dengan berbagai pihak, seperti pemerintah. Metode pelaksanaan PKM dilakukan melalui webinar interaktif dan pendampingan intensif berupa Focus Group Discussion (FGD) yang diadakan pada tanggal 12 Mei 2024. Tim PKM memberikan pelatihan dan konsultasi kepada Ibu Istianah beserta rekan-rekan bisnis, para pelaku UMKM di Kabupaten Pacitan. Kegiatan webinar juga melibatkan praktisi dalam bidang pemasaran, yaitu Bapak Handarbeni Setio Wicaksono. Hasil dari PKM ini adalah terjadinya peningkatan kesadaran mereka terhadap merek dan efektivitas pemasaran yang signifikan termasuk undangan untuk berpartisipasi dalam Fashion Fest 2024. Kegiatan ini mampu memberikan kontribusi update profil bisnis OG Jewelry menjadi UMKM go internasional lewat partisipasi unggulan pada Fashion Fest 2024 dan juga berhasil memodifikasi profil OG Jewelry di media sosial yang berdampak meningkatkan engagement dengan pelanggan